Increased Hb A2 values in an HIV-1-infected patient receiving antiretroviral drugs: A pitfall for thalassemia antenatal diagnosis - Sakorn Pornprasert (2018)
We report a human immunodeficiency virus-1 (HIV-1 )-infected couple, where the woman in the 11th week of gestation, carried a Hb E trait. She and her spouse were referred to tlie hemoglobinopathy counselors. Her spouse's blood was subsequently tested and showed an increased Hb A2value. However, his red cell indices and osmotic fragility test were different from those found in β-thalassemia β-thal) carriers. The β-thal genes were investigated further and no mutations were observed. Therefore, it is unlikely that he is a β-thal carrier and the increased Hb A2value is a result of receiving antirelroviral drugs. As antenatal thalassemia screening becomes more widespread, measuring the Hb A2values should be taken in all HIV-1-infected couples before the initiation of antiretroviral drugs to rule out misdiagnosis of β-thal. However, if these tests are not available, the results of the red cell indices and osmotic fragility test should be considered as they may provide great value for β-thal investigations.